PENGARUH RELATIONSHIP MARKETING, ONLINE CUSTOMER REVIEW DAN CONTENT MARKETING TERHADAP KEPUTUSAN PEMBELIAN LAYANAN INDRIVE DI SURABAYA - Sya’ban, Mochammad Rizqi; Nasution, Ute Chairuz; Pratiwi, Ni Made Ida (Maisyatuna, 2025)
This research is motivated by the development of digital technology which currently has a significant impact on the development of industry in Indonesia, one of which is the transportation industry. The development of this technology forces companies in the transportation industry to innovate in implementing digital-based marketing strategies in order to maintain, develop businesses, and improve customer purchasing decisions. In the context of digital marketing, there are several marketing strategies used in this study to improve customer purchasing decisions, namely relationship marketing, online customer reviews and content marketing. This study aims to determine and analyze the influence of relationship marketing, online customer reviews and content marketing on purchasing decisions for inDrive services in Surabaya. This study uses a quantitative research method, with a questionnaire distribution technique via Google Form. The respondents used in this study were 100 people obtained using a simple random sampling technique. Quantitative analysis includes validity and reliability tests, classical assumption tests, hypothesis tests including t-tests (partial), F-tests (simultaneous) and coefficient of determination tests (R2). The results of this study indicate that partially the variables of relationship marketing, online customer reviews and content marketing have a positive and significant effect on purchasing decisions for inDrive services in Surabaya. Simultaneously, the results show that the variables of relationship marketing, online customer reviews and content marketing have a positive and significant effect on purchasing decisions for inDrive services in Surabaya. Keywords: relationship marketing, online customer reviews, content marketing, purchasing decisions